Low‐dose rescue tirofiban in mechanical thrombectomy for acute cerebral large‐artery occlusion. (17th March 2020) - Yang, M.; Huo, X.; Gao, F.; Wang, A.; Ma, N.; Shi, H.; Chen, W.; Wang, S.; Wang, Y.; Miao, Z.
Abstract : Background and purpose: Tirofiban administration during mechanical thrombectomy (MT) remains controversial. The aim was to evaluate the safety and efficacy of a low‐dose rescue tirofiban regimen during MT for Chinese acute ischaemic stroke (AIS) patients. Methods: Patients from the ANGEL study, a multicentric, prospective registry study that included AIS patients who underwent MT owing to proximal large‐artery occlusion from June 2015 to December 2017, were collected. The patients were dichotomized into tirofiban and non‐tirofiban groups according to whether rescue tirofiban was performed during MT. Safety outcomes [symptomatic intracerebral haemorrhage (sICH), total intracerebral haemorrhage (ICH) and distal embolization] and efficacy outcomes (artery recanalization and functional outcomes at 3‐month follow‐up) were compared between groups using logistic regression analysis. Results: A total of 662 patients were included in this study, and 230 (34.7%) were in the tirofiban group. No significant differences in safety outcomes on sICH, total ICH and distal embolization and efficacy outcomes on artery recanalization and 3‐month functional independence were observed between the tirofiban and non‐tirofiban group in the entire cohort or the anterior circulation stroke or posterior circulation stroke patients ( P  > 0.05 for all groups). However, low‐dose rescue tirofiban was significantly correlated with 3‐month mortality reduction for posterior circulation stroke patients [adjusted hazard ratio 0.35 (0.14–0.92), P  = 0.03]. Conclusions: Low‐dose rescue tirofiban during MT was not associated with increased risk of sICH, ICH and distal embolization for AIS patients, and may be correlated with 3‐month mortality reduction for posterior circulation stroke.